EDUCATIONAL MANAGEMENT OF EDUCATIONAL CULTURE AND CHARACTER IN 3 PUBLIC ELEMENTARY SCHOOLS PILOTS BIREUEN - Nova, Nova; Nurdin, Diding (Universitas Pendidikan Indonesia, 2022)
Some of the problems of educational institutional management, especially in the out-of-school education path that are being faced today are: I) the high illiteracy rate in various age ranges, 2) there are still school-age children who are out of the school education system, 3) many elementary, junior high school, high school graduates who do not continue to a higher level, 4) the large number of the unemployed labor force population because they are unable to compete in the job market, 5) the heavy burden on families and communities in making ends meet due to poverty. The five main problems above, the Ministry of National Education has developed a countermeasure strategy that can be implemented in various pathways, types and levels of education, namely life skills-oriented education through a broad-based education approach. In the process of cultural education and the personality of the nation, learners actively develop pots. One of the latest national education policies in Indonesia is to implement education with the character of national values in Indonesian schools. In the process of cultural education and the personality of the nation, learners actively develop their potential, internalize and internalize the values of their personality by integrating into society, develop developing a more prosperous society life and developing a decent national life. Culture is a whole system of thoughts and feelings, actions and works produced by man in social life that are worthy of study. Through education that develops cultural values and national courage, students have similar values and personalities to themselves, able to apply these values in their lives as individuals, as members of society and as religious, ethnic, productive and creative citizens.Keywords: Education Management, Cultural, Educational Character